HUBUNGAN PENGETAHUAN DAN PERAN ORANG TUA (IBU) DENGAN PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI DI SMPN 2 UKUI KABUPATEN PELALAWAN - Syukrianti Syahda (Jurnal Doppler, 2020)
Poor personal hygiene behavior during menstruation, and the use of unhealthy sanitary pads are the main causes of reproductive tract infections (ISR). The highest incidence of Reproductive Tract Infection (ISR) in the world occurs in adolescence (35% -42%). Data from the Indonesia Demographic Health Survey (IDHS) in 2017 said that the behavior of adolescent girls in maintaining hygine during menstruation was still poor, at 63.9%. The purpose of this study was to determine the relationship of knowledge and the role of parents with female teenage personal hygiene during menstruation at SMU 2 Ukui in 2019. This study used analytic design and cross sectional approaches. The population in this study were all female students at SMU 2 Ukui who experienced menstruation, which were 254 people with a sample of 72 people with simple random sampling technique. The measuring instrument used was a questionnaire with research analysis used was univariate analysis and bivariate analysis. The results showed that there is a relationship of knowledge with personal hygiene during menstruation with p value 0.003 (p